EXECUTION OF DECISIONS OF THE INDUSTRIAL RELATIONS COURT WITH PERMANENT LEGAL FORCE (INKRACHT) - Daniel Ritonga; Achmad Fitrian; Gatut Hendro (Transpublika Publisher, 2022)
The research will discuss the execution of industrial relations court decisions with permanent legal force, aiming to reveal and analyze how the process of implementing industrial relations court decisions with permanent legal force and what factors hinder the execution of industrial relations court decisions with permanent legal force. This is a literature study using normative legal research. The data collected by library research, namely by the study of written information about the law that comes from various sources and is widely published and is needed in normative legal research. The findings highlight that the procedure for the execution of industrial relations court decisions that have permanent legal force has not been explicitly regulated in Law Number 2 of 2004 concerning Industrial Relations Dispute Settlement. However, Industrial Relations Dispute Settlement confirms that the Industrial Relations Court applies procedural law applicable to civil procedural law within the General Courts as stated in Article 57 of Industrial Relations Dispute Settlement. The lack of good faith on the part of the losing party to voluntarily carry out their obligations as stated in the verdict is one of the factors impeding the execution of the Industrial Relations Court's decision, which has permanent legal force. In addition, it is difficult for the winning party, in this case the workers, to determine which company assets can be executed against the losing party, and the execution cost is too high for the court to issue an execution order.